The treatment of multidirectional instability of the shoulder with a rehabilitation program: Part 1. Issue 4 (October 2016) - Watson, Lyn; Warby, Sarah; Balster, Simon; Lenssen, Ross; Pizzari, Tania
Background: The most commonly recommended initial treatment for multidirectional instability is a rehabilitation program. Although there is evidence to support the effect of conservative management on this condition, the published literature provides little information on the exercise parameters of such programs. In addition, current published rehabilitation programs for multidirectional instability do not focus on scapula stability or exercise drills into functional and sports-specific positions, which are often important aspects to consider in this patient population. Methods: The aim of this paper (Part 1) is to outline the first two stages of a six-stage rehabilitation program for the conservative management of multidirectional instability with a focus on scapula control and exercise drills into functional positions. Results and Conclusions: This clinical protocol is currently being tested for efficacy as part of a randomized controlled trial (Australian New Zealand Clinical Trials Registry #ACTRN12613001240730). The information in this paper and additional online supplementary files will provide therapists with adequate detail to replicate the rehabilitation program in the clinical setting.